2018
DOI: 10.3892/ijo.2018.4446
|View full text |Cite
|
Sign up to set email alerts
|

KRAB zinc-finger protein 382 regulates epithelial-mesenchymal transition and functions as a tumor suppressor, but is silenced by CpG methylation in gastric cancer

Abstract: Several studies have recently reported that KRAB zinc finger protein 382 (ZNF382) is downregulated in multiple carcinoma types due to promoter methylation. The exact role of ZNF382 in gastric carcinogenesis, however, remains elusive. In this study, we investigated the alterations and functions of ZNF382 in the pathogenesis of gastric cancer (GC). Semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR), quantitative (real-time) PCR (qPCR) and immunohistochemistry were carried out to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…As previously reported,12,14 the cells were treated with a DNA methyltransferase (DNMT) inhibitor,5-Aza-2ʹ-deoxycytidine (Aza) (Sigma-Aldrich, Steinheim, Germany), in the dark at a final concentration of 10 mmol/l for 3 days, and further treated with 100 nmol/l trichostatin A(TSA) (Cayman Chemical, Ann Arbor, MI, USA), a histone deacetylase inhibitor, for another 1 day. Other groups had cells treated only with Aza (Sigma-Aldrich) in the dark at a final concentration of 10 mmol/l for 3 days or TSA at a final concentration of 100 nmol/l for 1 day.…”
Section: Methodssupporting
confidence: 82%
“…As previously reported,12,14 the cells were treated with a DNA methyltransferase (DNMT) inhibitor,5-Aza-2ʹ-deoxycytidine (Aza) (Sigma-Aldrich, Steinheim, Germany), in the dark at a final concentration of 10 mmol/l for 3 days, and further treated with 100 nmol/l trichostatin A(TSA) (Cayman Chemical, Ann Arbor, MI, USA), a histone deacetylase inhibitor, for another 1 day. Other groups had cells treated only with Aza (Sigma-Aldrich) in the dark at a final concentration of 10 mmol/l for 3 days or TSA at a final concentration of 100 nmol/l for 1 day.…”
Section: Methodssupporting
confidence: 82%
“…ID4 promoter methylation was also correlated with the risk of prostate cancer [44,45]. Meanwhile, NOL4, PAX6, TRIM58, and ZNF382 promoter methylation was also associated with the occurrence of many cancers [46][47][48][49][50][51][52][53][54][55]. Figure 4: Kaplan-Meier survival curves for overall survival outcomes according to the risk cuto point for prognostic hypermethylated/ hypomethylated genes.…”
Section: Discussionmentioning
confidence: 98%
“…ZNF382 is also methylated and exhibits reduced expression in gastric cancer (GC) tissues. Pei et al showed that ZNF382 can reverse the process of epithelial to mesenchymal transition in GC cells through NOTCH signaling, further supporting its role as a tumor suppressor [ 17 ]. In esophageal squamous cell carcinoma (ESCC), the expression of ZNF382 was inhibited due to aberrant promoter methylation and ZNF382 methylation correlated with the level of ESCC differentiation.…”
Section: Discussionmentioning
confidence: 99%